Nightmare-Induced Atypical Midventricular Tako-Tsubo Cardiomyopathy - Veronica Fibbi; Piercarlo Ballo; Marco Nannini; Lorenzo Consoli; Tania Chechi; Andrea Bribani; Francesca Fiorentino; Leandro Chiodi; Alfredo Zuppiroli (Case Reports in Medicine)
Tako-Tsubo cardiomyopathy (TTC) is a reversible cardiomyopathy characterized by acute left ventricular segmental dysfunction, whose clinical presentation resembles that of acute myocardial infarction. The syndrome often follows a psychophysical stressful event and is characterized by echocardiographic evidence of akinesia of the left ventricular mid-apical segments. Atypical echocardiographic patterns of TTC have recently been described, often triggered by emotional stressors, rather than physical. In this report, we describe a case of atypical TTC triggered by an unusual stressor (recurrent nightmare) in a 45-year-old woman, with peculiar clinical presentation and evolution characterized by persistent loss of consciousness, neurological deterioration, absence of typical symptoms of TTC, and features suggestive of a hysterical crisis.